Implementing problem-based learning to improve students' learning outcomes: A classroom action research - Padia Haya; Syarifah Nur Siregar; Yenita Roza (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2025)
This study was motivated by the low mathematics learning outcomes of seventh-grade students at SMP Negeri 1 Ujungbatu in the 2024/2025 academic year. The purpose of this research was to improve the learning process and enhance mathematics achievement through the implementation of the Problem-Based Learning (PBL) model. This classroom action research was carried out in two cycles involving 34 students (17 female and 17 male) with heterogeneous abilities. The study focused on student learning activities and learning outcomes. Data were collected through observation sheets and learning achievement tests, and analyzed both quantitatively and qualitatively in a descriptive manner. The results showed a significant improvement in the learning process and student achievement after the application of the PBL model. The percentage of students who met the Criteria for Achievement of Learning Objectives increased gradually from 32.4% at the baseline to 50% in the first summative test, and further to 61.8% in the second summative test. These findings indicate that the implementation of the PBL model not only enhanced student engagement in the learning process but also contributed positively to improving mathematics learning outcomes among seventh-grade students at SMP Negeri 1 Ujungbatu.